1989
DOI: 10.2169/internalmedicine1962.28.612
|View full text |Cite
|
Sign up to set email alerts
|

Probucol-induced QT prolongation and torsades de pointes.

Abstract: Probucol administration of 4 weeks produced torsades de pointes associated with exacerbated QTinterval prolongation in a 36-year-old womanwith Romano-Wardsyndrome. With discontinuance of probucol, the QTinterval corrected for rate shortened from 620 msec to 500 msec and ventricular ectopic beats disappeared completely. Although probucol is known to prolong the QTinterval, associated ventricular tachyarrhythmia has not been reported in humansas yet. This case suggests that one should be very careful in the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…In addition, probucol prolongs the QT interval of the electrocardiogram. Such a change in QT interval is associated with malignant arrhythmias . Strikingly, in this study, we not only found anti‐oxidant activities of probucol, but also its destruction of endothelial cell–cell connections on the early‐stage AS model (Figure C).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, probucol prolongs the QT interval of the electrocardiogram. Such a change in QT interval is associated with malignant arrhythmias . Strikingly, in this study, we not only found anti‐oxidant activities of probucol, but also its destruction of endothelial cell–cell connections on the early‐stage AS model (Figure C).…”
Section: Discussionsupporting
confidence: 58%
“…Such a change in QT interval is associated with malignant arrhythmias. [ 60,61 ] Strikingly, in this study, we not only found anti-oxidant activities of probucol, but also its destruction of endothelial cell-cell connections on the early-stage AS model (Figure 5 C). The destruction effect of probucol on ECs monolayer integrity may promote the infi ltration of oxidized LDL and infl ammatory cells which are the initial stage of AS progression.…”
Section: Discussionsupporting
confidence: 49%
“…Probucol is a cholesterol-lowering drug that has been found to cause long QT syndrome and torsades de pointes arrhythmia in patients and sudden cardiac death in experimental animals (Elharrar et al, 1979;McCaughan, 1982;Browne et al, 1984;Dujovne et al, 1984;Matsuhashi et al, 1989;Tamura et al, 1994;Reinoehl et al, 1996;Hayashi et al, 2004). Our data indicate that chronic probucol exposure reduces the hERG current with an IC 50 of 10.6 M and reduces native I Kr with an IC 50 of 20.6 M. We chose 48-h treatment of cells with probucol because the turnover of the hERG channel occurs at a rather slow rate (approximately 11 h) (Ficker et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…274 Yet, case reports of QT prolongation and development of torsade de pointes or syncope were published. 275,276 Results of additional investigations suggest that QTc prolongation is likely to appear in female patients and in patients with long baseline QTc or with low serum albumin levels. 277,278…”
Section: Definite Associationmentioning
confidence: 99%